PERTUSSIS- EPIDEMIOLOGY, DIAGNOSTICS, TREATMENT. LITERATURE REVIEW - Adrianna Perzanowska; Zuzanna Tomaszewska; Anna Zielińska; Julia Ciechanowicz; Stanisław Ciechanowicz; Julia Dura; Marika Gutowska; Piotr Kupidłowski; Agata Nowacka; Aleksandra Przybylska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose. The bacterium Bordetella pertussis causes pertussis, an infectious respiratory disease. Despite the introduction of an expanded vaccination programme over the past decades, pertussis remains a public health concern. This literature review aims to compare clinical and laboratory diagnostics. Additionally, we will focus on the impact of the Covid-19 pandemic on the increase in cases of the disease. State of knowledge. The illness has three phases: an initial stage lasting one to two weeks; a second stage characterised by coughing fits lasting up to four weeks; and a final recovery phase. Although antibiotics used during the second stage reduce infectiousness, it is unclear whether they reduce the duration of illness. During the first two weeks, patients may experience flu-like symptoms. Culture testing is considered the gold standard, providing 100% specificity. This enables identification of the strain and antibiotic susceptibility testing. This method is most effective within the first two weeks of illness, while viable bacteria are still present. The number of cases fluctuates from year to year, but there has been a marked decrease among young children and an increase among adolescents and adults. Following the discontinuation of protective measures against SARS-CoV-2, significant pertussis outbreaks have occurred. Material and methods. This review analyzes the epidemiology, diagnosis, and treatment of whooping cough, with a particular focus on the years from 2019 to the present. The article was based on sources from scientific databases such as PubMed. Summary. Researchers have linked the increase in pertussis cases in recent years to the lifting of restrictions during the post-Covid period. It is therefore important to raise public awareness of the need for revaccination and to continue scientific research into the epidemiology and diagnosis of this disease.